BINA KELUARGA REMAJA (BKR) DALAM RANGKA MENINGKATKAN POLA ASUH REMAJA YANG BENAR DAN TERARAH - Hidayanto, Fajar (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Family the first and top learning place for every teenager. Parenting way will affect the development of teenager's characters. But, not all parents understand how to deal with teenager correctly, such as parents at Dusun Jati, Kelurahan Gerbosari, Kecamatan Samigaluh, Kabupaten Kulon Progo, Provinsi D.I. Yogyakarta. So, they need an education about parenting. Based on these circumstances, the authors organized a " Bina Keluarga Remaja (BKR)" as a community service activities. Parents are given educational material in six sessions, those are definition of teenager, the importance of parents role, the importance of sex education for teenager, the importance of parental supervision, the role of peers, and the role of parents to help tenageer to recognize himself. The service activities managed to increase the knowledge of parents in tenaager growth fostering correctly and focused, in order to build a quality family.